The Effectiveness Of Buerger Allen Exercise On Decreasing ABI Value In Diabetes Mellitus Patients With Virginia Henderson's Nursing Model Theory Approach In The Covid-19 Pandemic - Mulia Mayangsari; Mohammad Lutfi (Universitas STRADA Indonesia, 2021)
Diabetes mellitus (DM) is a metabolic disorder, with increased levels of sugar in the blood. Untreated elevated blood sugar levels can lead to micro/macrovascular complications and neuropathy. One of the chronic complications of diabetes mellitus type 2 is diabetic foot ulcers. This study uses a Quasy Experiment design of two variables studied with a pre-test and post-test control design approach. The sampling technique used purposive sampling on 45 respondents in the intervention group who were given the Buerger Allen exercise and 45 respondents in the control group who were not given the intervention. The results showed that there was a significant difference in the value of the Ankle Brachial Index (ABI) before and after being given the Buerger Allen Exercise treatment, namely p <0.05. In conclusion, buerger allen exercise was effective in increasing the value of the Ankle Brachial Index (ABI).